Care engagement with healthcare providers and symptom management self-efficacy in women living with HIV in China: secondary analysis of an intervention study - Wei-Ti Chen; Chengshi Shiu; Lin Zhang; Hongxin Zhao (BMC, 2022)
Abstract Background Symptom management self-efficacy is a prerequisite for individuals to fully manage their symptoms. The literature reports associations between engagement with healthcare providers (HCPs), internalized stigma, and types of self-efficacy other than symptom management. However, the factors of symptom management self-efficacy are not well understood. This study aimed to investigate the relationship among engagement with HCPs, internalized stigma, and HIV symptom management self-efficacy in Chinese women living with HIV (WLWH). Methods This current analysis was part of the original randomized control trial, we used data collected from 41 women living with HIV (WLWH) assigned to an intervention arm or a control arm from Shanghai and Beijing, China, at baseline, Week 4 and Week 12. The CONSORT checklist was used. The study was registered in the Clinical Trial Registry (#NCT03049332) on 10/02/2017. Results The results demonstrate that HCPs should increase engagement with WLWH when providing care, thereby improving their symptom management self-efficacy. The results suggested that participants' engagement with HCPs was significantly positively correlated with their HIV symptom management self-efficacy in the latter two time points. Internalized stigma was significantly negatively correlated with HIV symptom management self-efficacy only at the 4-week follow-up. Conclusions This study demonstrated the positive effect of engagement with HCPs on WLWHs' symptom management self-efficacy as well as the negative effect of internalized stigma on symptom management self-efficacy. Future research can further test the relationship between the three key concepts, as well as explore interventions to decrease internalized stigma.